Illegal Logging Crime in Indonesia - Bambang Sukamto; Nur Aidah; Mipasya Ratu Plamesti; Zahrah Nurhafizah; Nino Agung Perdana (AMCA, 2025)
Then there was a discussion about the current legal policy and its application regulations are not yet solved various problems, especially in the environmental sector. From time to time, the UUPPLH shows that it is not working optimally, on the other hand, environmental technology and crime are increasingly developing and developing, which eventually lead to effects of international scope, namely illegal mining, illegal fishing and illegal. logging It was later classified as white-collar crime, which still happens today. Standard legal research style is applied here. The problem approaches applied here are legal approach, conceptual approach and jurisprudence. The difficulty in enforcing the crime of illegal logging is due to several jurisdictions, namely: lack of laws, law enforcement, anything to do with human values, anything to do with supply and demand, then poor quality personnel.